DO PLANNING QUALITY AND IMPLEMENTATION CAPACITY DRIVE NON-TAX STATE REVENUE UNDER FISCAL SUPERVISION? - Krisnandono, Diananto; Wati, Lela Nurlaela; Yuli, Rama (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Non-tax state revenue (NTSR) strengthens Indonesia’s fiscal capacity; however, research on governance mechanisms for service-based NTSR optimization, especially the Ministry of Finance's role, remains scarce. This study fills this gap by exploring fiscal supervision's moderating effect on the NTSR management-revenue optimization link. A qualitative systematic literature review (SLR) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework synthesizes 28 articles (2010–2025) and relevant reports. Thematic content analysis identifies patterns linking planning accuracy, service execution, governance quality, and supervisory mechanisms to revenue performance. The findings show that NTSR optimization is driven by integrated managerial functions (planning, actuating, and controlling), with realistic targets and effective service delivery boosting revenue. However, these factors alone do not ensure optimal outcomes. Fiscal supervision moderate governance by enhancing accountability, reducing information asymmetry, improving internal controls, and ensuring compliance across ministries. Effective supervision amplifies the impact of planning and execution on NTSR optimization, supporting sustainable revenue. This study uniquely conceptualizes supervision as a moderating institutional mechanism in service-based NTSR governance. It contributes to public financial management and revenue governance literature by integrating state revenue theory and managerial function perspectives into a unified model. Practically, the findings offer policy insights for adaptive, performance-oriented NTSR supervisory systems. This study is limited to service-based NTSR and qualitative synthesis; future research should use quantitative methods to test the moderating framework across broader NTSR sectors.